Developing CISAR (Two-Mode Chain Story Cards) to Facilitate Hybrid Learning - Fina Zakiyatun Nufus; Rahmati Putri Yaniafari; Hasti Rahmanigtyas (Institut Agama Islam Negeri Madura, 2023)
This research was conducted to develop learning media that can assist tenth graders in Indonesia in practicing speaking in English and improve their grammar knowledge, particularly when studying recount and narrative texts. The instructional media development was carried out using the R&D research design. The research began with investigating students’ language learning difficulties by observing them in class and interviewing their teacher. This was then followed by product development, validation and tryout before the product was finalized. The research instruments used for developing and revising the media were field notes, expert validation sheets, and a questionnaire that measured the acceptability of the media. The products developed are 56 pieces of cards named CISAR (Chain Story Cards), one teacher manual, and one student manual. Based on the results of experts’ validations, the media has met the accessibility and appropriateness criteria but required a few revisions to meet practicality requirements. Meanwhile, the small scale tryout results involving thirty-six tenth graders of a public senior high school in East Java, Indonesia, CISAR is feasible in its design, language, and has suitable material for the target users since the design considers age-appropriacy, the language is adjusted to the level of proficiency of tenth graders, and the materials follow the syllabus of tenth graders. However, improvements to the manual book were required to make the cards easier to use. Feedback given by the tryout participants confirms that the developed cards serve their intended purposes of helping tenth graders learn speaking and grammar